Peningkatan Hasil Belajar Menulis Surat Pribadi dengan Metode Pembelajaran Think Talk Write (TTW) - Siti Nurul Fatimah; Ahmad Khoerul Saleh; Imam Agus Basuki (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2023)
Writing is one of the most complex skills in learning Indonesian. When writing has gone through the process of listening, speaking, and reading. Therefore, the purpose of learning Indonesian is for students to be able to manage aspects of language proficiency. However, it is difficult for most students to learn Indonesian, especially by writing personal letters. Based on data from 31 students in Class VII-E of SMPN 7 Kediri, only 13 students met the minimum completeness criteria with a score of 75. The main problem in this study was the low learning achievement of students in class VII-E of SMPN 7 Kediri in writing letters. This is caused by students and teachers. Based on these factors, to overcome the problem, the researcher applied the Think Talk Write (TTW) learning method to write personal letters. The Think Talk Write (TTW) learning method is said to be able to improve letter writing skills. The average value of students after being given the Think Talk Write (TTW) treatment increased from pre-cycle 70.96, cycle 1 75.8, and cycle 2 83.5. Thus based on the results of the study it can be concluded that the application of the Think Talk Write (TTW) method can improve the ability to learn to write personal letters. This learning method should be used by teachers because it can improve student learning outcomes, especially the learning outcomes of writing personal letters.